Selective Protein Hyperpolarization in Cell Lysates Using Targeted Dynamic Nuclear Polarization. Issue 36 (28th June 2016) - Viennet, Thibault; Viegas, Aldino; Kuepper, Arne; Arens, Sabine; Gelev, Vladimir; Petrov, Ognyan; Grossmann, Tom N.; Heise, Henrike; Etzkorn, Manuel
Abstract: Nuclear magnetic resonance (NMR) spectroscopy has the intrinsic capabilities to investigate proteins in native environments. In general, however, NMR relies on non‐natural protein purity and concentration to increase the desired signal over the background. We here report on the efficient and specific hyperpolarization of low amounts of a target protein in a large isotope‐labeled background by combining dynamic nuclear polarization (DNP) and the selectivity of protein interactions. Using a biradical‐labeled ligand, we were able to direct the hyperpolarization to the protein of interest, maintaining comparable signal enhancement with about 400‐fold less radicals than conventionally used. We could selectively filter out our target protein directly from crude cell lysate obtained from only 8 mL of fully isotope‐enriched cell culture. Our approach offers effective means to study proteins with atomic resolution in increasingly native concentrations and environments. Abstract : Directing polarization : By using a biradical‐labeled ligand, dynamic nuclear polarization (DNP) can be efficiently and very specifically directed to a target protein. This behavior makes it possible to filter out the signal of the target protein from a large background (see picture), enabling a selective solid‐state NMR characterization in increasingly native environments such as found in crude cell lysates.